A circular RNA vector for targeted plant gene silencing based on an asymptomatic viroid. (19th August 2022) - Marquez‐Molins, Joan; Hernandez‐Azurdia, Andrea Gabriela; Urrutia‐Perez, María; Pallas, Vicente; Gomez, Gustavo
SUMMARY: Gene silencing for functional studies in plants has been largely facilitated by manipulating viral genomes with inserts from host genes to trigger virus‐induced gene silencing (VIGS) against the corresponding mRNAs. However, viral genomes encode multiple proteins and can disrupt plant homeostasis by interfering with endogenous cell mechanisms. To try to circumvent this functional limitation, we have developed a silencing method based on the minimal autonomously‐infectious nucleic acids currently known: viroids, which lack proven coding capability. The genome of Eggplant latent viroid, an asymptomatic viroid, was manipulated with insertions ranging between 21 and 42 nucleotides. Our results show that, although larger insertions might be tolerated, the maintenance of the secondary structure appears to be critical for viroid genome stability. Remarkably, these modified ELVd molecules are able to induce systemic infection promoting the silencing of target genes in eggplant. Inspired by the design of artificial microRNAs, we have developed a simple and standardized procedure to generate stable insertions into the ELVd genome capable of silencing a specific target gene. Analogously to VIGS, we have termed our approach viroid‐induced gene silencing, and demonstrate that it is a promising tool for dissecting gene functions in eggplant. Significance Statement: We developed a standardized viroid‐based procedure (termed VdIGS) for targeted silencing of eggplant genes. Modified ELVd variants (with insertions up to 42 nt) are able to replicate and induce systemic infection in host plants. This innovative approach constitutes the first use of biological forms of viroids as a tool for plant biotechnology.